2022
DOI: 10.14218/jcth.2022.00052
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Metabolic-associated Fatty Liver Disease: A Clinical Update

Abstract: The intricate relationship between metabolic-associated fatty liver disease (MAFLD) and maternal complications has rapidly become a significant health threat in pregnant women. The presence of MAFLD in pregnancy increases the maternal risk of metabolic complications and comorbidities for both mother and baby. The preexistence or development of MAFLD in pregnancy is a complex multifactorial disorder that can lead to further complications for mother and baby. Therefore, as pregnant women are severely underrepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 91 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Metabolic dysfunction–associated steatotic liver disease (MASLD) (previously known as non-alcoholic steatohepatitis; NAFLD) is currently the most frequent chronic liver disease worldwide [ 78 ] and includes a spectrum from simple steatosis to hepatocellular injury and fibrosis. The prevalence of MASLD in pregnancy has nearly tripled in the last decade and is independently associated with a higher incidence of hypertensive complications, post-partum hemorrhage, pre-eclampsia HELLP syndrome, and preterm birth [ 79 81 ].…”
Section: Coincidental Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic dysfunction–associated steatotic liver disease (MASLD) (previously known as non-alcoholic steatohepatitis; NAFLD) is currently the most frequent chronic liver disease worldwide [ 78 ] and includes a spectrum from simple steatosis to hepatocellular injury and fibrosis. The prevalence of MASLD in pregnancy has nearly tripled in the last decade and is independently associated with a higher incidence of hypertensive complications, post-partum hemorrhage, pre-eclampsia HELLP syndrome, and preterm birth [ 79 81 ].…”
Section: Coincidental Liver Diseasesmentioning
confidence: 99%
“…The prevalence of MASLD in pregnancy has nearly tripled in the last decade and is independently associated with a higher incidence of hypertensive complications, post-partum hemorrhage, pre-eclampsia HELLP syndrome, and preterm birth [ 79 81 ]. Treatment in pregnancy mainly involves nutritional measures and physical activity [ 78 ].…”
Section: Coincidental Liver Diseasesmentioning
confidence: 99%
“…Lasting effects on the prevalence of metabolic diseases in the next generation are exerted by maternal obesity or overnutrition during pregnancy or lactation. These include non-alcoholic fatty liver disease (also called metabolicassociated fatty liver disease), non-alcoholic steatohepatitis, obesity, diabetes, chronic kidney disease, hypertension, and cardiovascular disease [21,[64][65][66][67][68][69][70]. Peng demonstrated that offspring born to mothers who had consumed high fat diets displayed a disruption of lipid homeostasis, which was accompanied by altered methionine and abnormal one-carbon metabolism in the livers of offspring [71].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Studies have reported an accumulation of liver cholesterol and triacylglycerides (TAGs) during the gestational period, as a mechanism involved in the regulation of proper fetal development in cases of maternal malnourished conditions [ 2 , 5 ]. Additionally, in response to overfeeding with high-fat diets, and obesity there is an increase of FFA acid uptake by the liver, as well as an increased lipogenesis and a decreased FA oxidation, leading to ectopic triglyceride deposition in the liver [ 6 ]. Notwithstanding, the understanding of liver lipid metabolism during pregnancy remains incomplete.…”
Section: Introductionmentioning
confidence: 99%